Microstructure and corrosion behavior of AlCoCrFeNiSi0.1 high-entropy alloy. (November 2019) - Xiang, C.; Zhang, Z.M.; Fu, H.M.; Han, E.-H.; Zhang, H.F.; Wang, J.Q.
Abstract: The microstructure and corrosion behavior of AlCoCrFeNiSi0.1 high-entropy alloy are investigated. The alloy was prepared by vacuum arc melting and subsequent injection casting. Two different phases, including one disordered BCC (A2) phase and one ordered BCC (B2) phase, are identified in this alloy. The alloy shows a typical equiaxed dendritic microstructure, both of the dendritic and interdendritic regions have an (Al, Ni)-rich matrix with B2 structure and (Cr, Fe)-rich precipitates with A2 structure. The precipitates present different morphologies in the dendritic and interdendritic regions, whereas the chemical composition and crystal structure are very similar. With regard to the corrosion behavior in deaerated 3.5 wt% NaCl solution, the pits were formed at the dendrites, and the selective dissolution of the dendrites could be mainly ascribed to the lower Cr content and galvanic coupling between the dendrites and the interdendrites. The alloy exhibits an active-passive corrosion behavior in deaerated 0.5 mol/L H2 SO4 solution. The preferential dissolution of the A2 phase is more severe than the B2 phase. The correlation between chemical composition, microstructure, and corrosion behavior is well illustrated. Highlights: The AlCoCrFeNiSi0.1 alloy has a disordered BCC phase and an ordered BCC phase. The AlCoCrFeNiSi0.1 alloy exhibits a typical equiaxed dendritic microstructure. Selective dissolution of the (Cr, Fe)-rich precipitates occurred in H2 SO4 solution. The relationship between the microstructure and corrosion behavior is elucidated.